A Cross-sectional Study Unveiling the Enduring Cost Burden of Diabetes and Hypertension Management in Bangladesh and its Association with Lifestyle Modifications (Dhaka University Journal of Pharmaceutical Sciences, 2026)
Diabetes mellitus and hypertension constitute major non-communicable diseases in Bangladesh, contributing substantially to morbidity, mortality, and economic burden, with limited evidence on medication costs and lifestyle modifications. A multi-stakeholder cross-sectional study was surveyed on 456 participants in Bangladesh, with data collected from Dhaka Medical College Hospital, selected Dhaka city pharmacy areas, professional workplaces, and online platforms using structured questionnaires. Among patients, the majority were aged 40–60 years (57.36%), female (52.83%) and from urban areas (84.53%). Hypertension was alone the most prevalent condition (30.94%), followed by diabetes (29.43%) and comorbid diabetes with hypertension (23.02%). Our study revealed that monthly medication expenses mostly ranged from BDT 1,000 to 5,000, as stated by 50.94% of patients, whilst 13.21% had costs above BDT 5,000. Chi-square analysis demonstrated significant correlations between monthly medication expenses incurred and affordability status (χ²=11.57, p=0.040), disease condition (χ²=48.63, p